Derivation and validation of the short version of the Malaysian oral health impact profile - Saub, R.; Locker, D.; Allison, P. (2005)
Objectives: This paper describes the development of a short version of the Malaysian Oral Health Impact Profile. Methods: The 45-item OHIP(M) was shortened using a method known as the 'item frequency method'. Here, the two most frequently reported items from each of the seven OHIP(M) subscales were chosen to form the short version, designated as the S-OHIP(M). Field testing was conducted to assess the effect of different modes of administration (mail versus interview) of the short form and to test its measurement properties (reliability and validity). A total of 206 respondents completed the questionnaire. In order to carry out test-retest analysis, a second administration was carried out 15 days after the first administration on a selected subsample. Results: The mail questionnaire had a lower response rate and a higher percentage of missing data than the interview administered questionnaire. However, the mail mode of administration resulted in higher scores than interview. Cronbach's alpha was 0.89 and the ICC was also 0.89. All hypotheses developed to assess validity were confirmed. Conclusion: The S-OHIP(M) was found to be valid and reliable and appropriate for use in the cross-sectional studies in Malaysian adult populations.